Mental health and primary dysmenorrhea: a systematic review - Zahra Bajalan; Farnoosh Moafi; Mohammad MoradiBaglooei; Zainab Alimoradi (Taylor & Francis Group, 2019)
Several factors including demographic, reproductive, lifestyle, psychological and social factors can affect incidence and severity of primary dysmenorrhea. This study aimed to systematically review the psychological risk factors associated with primary dysmenorrhea. Embase, ISI web of knowledge, ProQuest, Science Direct, Scopus and PubMed central were searched using keywords related to risk factors and primary dysmenorrhea. Observational studies, published in English after 2000, focusing solely on psychological factors affecting primary dysmenorrhea were included. The search process retrieved 11,928 potential related articles. Thirty three articles met inclusion criteria and were assessed for final synthesis. The STROBE checklist was used to quality assessment of studies. Results of study showed that few studies had investigated relationship between dysmenorrhea and most psychological disorders. Most studies have investigated the relationship between dysmenorrhea and depression, anxiety, stress, alcohol abuse and somatic disorders. So, further studies are needed to investigate relation between most psychological disorders with primary dysmenorrhea. Significant relationship between some mental health components such as depression, anxiety and stress with primary dysmenorrhea shows the importance of psychological assessment before the choice of therapeutic methods. Also, the feasibility of designing and evaluating the effectiveness of the use of psychotherapy interventions for the treatment of primary dysmenorrhea as alternative therapies can be considered.